Comprehensive investigation of the content and the origin of matrine-type alkaloids in Chinese honeys. (15th February 2023) - Wang, Zhiying; Zu, Tiehong; Huang, Xuezhe; Jiang, Xiaolin; Jia, Guangqun; Xu, Jinzhong; Cui, Zongyan; Zhu, Fengmei; Zhang, Jinjie; Li, Jun; Cao, Yanzhong
Highlights: HPLC-MS/MS method developed for determination of four matrine-type alkaloids (MAs). 567 Chinese honey samples were analyzed with the detection rate of 61%. 100 % Sophora viciifolia Hance ( Sv H) honey samples detected with the average content of 1183.3 μg/kg. Positive correlation found (R 2 = 0.737) between MAs and pollen frequency of Sv H. Sv H identified as the source of MAs in Chinese honeys. Abstract: A HPLC-MS/MS method for simultaneous determination of four matrine-type alkaloids (matrine, oxymatrine, sophocarpine and sophoridine) in honey was established and was applied to 567 Chinese honey samples. The overall detection rate was 61.0 % and all eight Sophora viciifolia Hance honey samples were detected with the average content of 1183.3 μg/kg. Among 383 Acacia honey samples, matrine-type alkaloids have the highest detection rates in Gansu (98.8 %) and Shaanxi (86.5 %) provinces, which were significantly correlated with the distribution of S. viciifolia Hance. Moreover, matrine-type alkaloids in fruits and flowers of S. viciifolia Hance were as high as 7.06 g/kg and 2.65 g/kg respectively. The melissopalynological analysis showed that the concentration of oxymatrine was positively correlated with the pollen frequency of S. viciifolia Hance (R 2 = 0.737) in representative Acacia honey samples. It can be concluded that the matrine-type alkaloids in Chinese honeys come from the nectariferous plants S. viciifolia Hance.